2018
DOI: 10.3389/fncir.2018.00112
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Irradiation-Induced Hippocampal Abnormalities in Rats Evaluated Using Manganese-Enhanced MRI

Abstract: The aim of this study was to characterize hippocampal abnormalities in rats after prenatal x-ray irradiation using manganese-enhanced MRI (MEMRI). All radiation-exposed rat brains showed a reduced volume with prominent dilatation of lateral ventricles. Moreover, MEMRI-enhanced areas within the hippocampus were reduced in volumes by approximately 25% of controls, although the entire volume of hippocampus was decreased by approximately 50% of controls. MEMRI signals were enhanced strongly in the hilus and granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this study, we observed a significant decrease in hippocampal SI after irradiation, which may be due to apoptosis. Similarly, Saito et al [37] observed that MEMRI signals in the CA1/2 regions of the hippocampus disappeared after prenatal X-ray irradiation. Apoptosis was related to irradiation dose, with the higher dose associated with more obvious apoptosis and lower MEMRI signals.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, we observed a significant decrease in hippocampal SI after irradiation, which may be due to apoptosis. Similarly, Saito et al [37] observed that MEMRI signals in the CA1/2 regions of the hippocampus disappeared after prenatal X-ray irradiation. Apoptosis was related to irradiation dose, with the higher dose associated with more obvious apoptosis and lower MEMRI signals.…”
Section: Discussionmentioning
confidence: 79%
“…In another study, 3-week-old rats exposed to prenatal radiation showed a decrease in brain volume, significant expansion of the lateral ventricles, a decrease in the MEMRIenhanced area in the hippocampus, and disappearance of the MEMRI signal in the CA1/2 region due to destruction of the CA1/2 pyramidal cell layer by invading ectopic cell clusters. However, Mn 2+ enhancement was still present in the CA3 and DG regions, mainly due to glial cell activation, but was below normal levels (165). In a study of tumor radiotherapy, MEMRI detected cellular changes at an early stage (24 h) (166).…”
Section: Chemical and Physical Brain Injurymentioning
confidence: 97%